(New page: We are given the input to an LTI system along with the system's impulse response and told to find the output y(t). Since the input and impulse response are given, we simply use convolutio...)
 
 
(5 intermediate revisions by the same user not shown)
Line 1: Line 1:
 
We are given the input to an LTI system along with the system's impulse response and told to find the output y(t).  Since the input and impulse response are given, we simply use convolution on x(t) and h(t) to find the system's output.
 
We are given the input to an LTI system along with the system's impulse response and told to find the output y(t).  Since the input and impulse response are given, we simply use convolution on x(t) and h(t) to find the system's output.
  
  <math>y(t) = h(t) * x(t) = \int_{-\infty}^\infty h(t-\tau)x(t)d\tau</math>
+
  <math>y(t) = h(t) * x(t) = \int_{-\infty}^\infty h(t-\tau)x(t)d\tau</math> ('''''COMMUTATIVE PROPERTY''''')
  
  
Line 8: Line 8:
 
<math>
 
<math>
 
\begin{align}
 
\begin{align}
  y(t) & = \int_{-\infty}^\infty e^{-t-\tau}u(t-\tau)u(\tau-1)d\tau \\
+
  y(t) & = \int_{-\infty}^\infty e^{-(t-\tau)}u(t-\tau)u(\tau-1)d\tau \\
       & = \int_1^\infty e^{-t-\tau}u(t-\tau)d\tau \\
+
       & = \int_1^\infty e^{-(t-\tau)}u(t-\tau)d\tau \\
       & = \int_1^{t} e^{-t-\tau}d\tau  \\  
+
       & = \int_1^{t} e^{-(t-\tau)}d\tau  \\  
 
       & = e^{-t}\int_1^{t} e^{\tau}d\tau  \\  
 
       & = e^{-t}\int_1^{t} e^{\tau}d\tau  \\  
 
       & = e^{-t}(e^{t} - e) \\
 
       & = e^{-t}(e^{t} - e) \\
Line 21: Line 21:
  
 
<math>y(t) = 0\, \mbox{ for } t < 1</math>
 
<math>y(t) = 0\, \mbox{ for } t < 1</math>
 +
 +
 +
<math>\therefore y(t) =
 +
\begin{cases}
 +
  1-e^{-(t-1)},  & \mbox{if }t\mbox{ is} > 1 \\
 +
  0, & \mbox{if }t\mbox{ is} < 1
 +
\end{cases}</math>

Latest revision as of 15:56, 30 June 2008

We are given the input to an LTI system along with the system's impulse response and told to find the output y(t). Since the input and impulse response are given, we simply use convolution on x(t) and h(t) to find the system's output.

$ y(t) = h(t) * x(t) = \int_{-\infty}^\infty h(t-\tau)x(t)d\tau $  (COMMUTATIVE PROPERTY)


Plugging in the given x(t) and h(t) values results in:

$ \begin{align} y(t) & = \int_{-\infty}^\infty e^{-(t-\tau)}u(t-\tau)u(\tau-1)d\tau \\ & = \int_1^\infty e^{-(t-\tau)}u(t-\tau)d\tau \\ & = \int_1^{t} e^{-(t-\tau)}d\tau \\ & = e^{-t}\int_1^{t} e^{\tau}d\tau \\ & = e^{-t}(e^{t} - e) \\ & = 1-e^{-(t-1)}\, \mbox{ for } t > 1 \end{align} $


Since x(t) = 0 when t < 1:

$ y(t) = 0\, \mbox{ for } t < 1 $


$ \therefore y(t) = \begin{cases} 1-e^{-(t-1)}, & \mbox{if }t\mbox{ is} > 1 \\ 0, & \mbox{if }t\mbox{ is} < 1 \end{cases} $

Alumni Liaison

Prof. Math. Ohio State and Associate Dean
Outstanding Alumnus Purdue Math 2008

Jeff McNeal